TAFSIR ILMI: Sejarah dan Konsepsinya - Sulhadi, Asep (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2022)
When the wave of Hellenism entered the Islamic world through the translation of scientific books during the Abbasid dynasty, especially during the reign of al-Ma'mun, there was a tendency to interpret the Qur'an with scientific theories or later known as scientific interpretation. This model of scientific interpretation has become a debate among scholars both in classical and modern times. Among them there are those who support and some who reject. In this simple article, the author will explore matters related to scientific interpretation in terms of understanding, emerging history, concepts and pros and cons that occur among scholars. Keywords: Qur’an, Tafseer, scientific interpretation